Akuntabilitas Pengelolaan Dana Bantuan Operasional Sekolah (Studi Kasus SDN Pringgowirawan 02 Jember) - Tutus Julantika; Taufik Kurrohman; Djoko Supatmoko (UPT Penerbitan Universitas Jember, 2017)
This research has two purposes i.e. to know the application of accountability system within the management of AccountabilityOf School Operational Assistance (BOS) fund and how the responsibility of Accountability Of School Operational Assistance(BOS) fund is used foward Pringgowirawan 02 Elementary school Sumberbaru in 2014 method of collecting data in theresearch is done through interview with the school principal and the chamberlain of Accountability Of School OperationalAssistance (BOS). Besides, the researcher also uses direct observation foward the school area. The goal of this research is themanagement of Accountability Of School Operational Assistance (BOS) fund which is gained from the total planned and thetotal used of Accountability Of School Operational Assistance (BOS) fund itself. The compatibility of Accountability Of SchoolOperational Assistance (BOS) fund used can be seen from the ratio shown. Ratio in this research is the number which isdemonstrated the ability of school to use Accountability Of School Operational Assistance (BOS) fund based on the plannedAccountability Of School Operational Assistance (BOS) fund in the earlier semester.